Analisis Pengunaan Kata Keji dalam Film Bumi Manusia: Kajian Sosiolinguistik - Nuraini Nuraini; Achmad Yuhdi (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
This article aims to provide an initial view of the use of abusive words in the film "Bumi Manusia" and can be used as a reference in analyzing the use of abusive words in this film. Therefore, an analysis of the use of the word heinous in this film can provide a deeper understanding of the social conditions depicted in the film. Sociolinguistic studies study the relationship between language and society, and an analysis of the use of the word obscenity in the film "Bumi Manusia" can contribute to this field by enriching our understanding of language use in social contexts. Thus, research on the analysis of the use of the word heinous in the film "Bumi Manusia" from a sociolinguistic perspective is important to do to enrich the understanding of language and society in the context of the film. The research subject is the Earth of Mankind film with an analysis of vile or swear words that has not been studied much. Meanwhile, research analysis on the use of heinous words in the film Bumi Manusia: a sociolinguistic study focuses on the use of vicious words in dialogue in the film Bumi Manusia and how the use of these abusive words is influenced by the social context, such as the speaker’s social status and the communication situation that occurs. This study uses qualitative research as revealed by Bogdan and Taylor, which is a research procedure that produces descriptive data in the form of written or spoken words from the person or behavior observed by the researcher. To provide data, basic listening techniques are used with advanced free listening techniques and note taking techniques.